Use anger to guide your stock market decision-making: results from Pakistan - Abdul Moueed; Ahmed Imran Hunjra (Cogent Economics & Finance, 2020)
We assess the role of psychological and social factors in the decision-making of investors mediated by risk perception. We use a questionnaire survey to collect data from 470 individuals who have invested in firms listed at Pakistan Stock Exchange. We use confirmatory factor analysis to refine the instrument and structural equation model for hypothesis testing. We find that psychological and social factors play a significant role in investors' decision-making. Specifically, anger, fear and a positive mood positively affect investors' decision-making whereas stress, social interaction and herding produce negative effects. Furthermore, risk perception plays a mediating role between psychological factors, social factors and the investment decision.
Keywords: 330; Investment decision; risk perception; psychological factors; anger; fear; social interaction; individual investors